Isolation and characterization of bacteria degrading Sumandak and South Angsi Oils - Ainon Hamzah; Amir Rabu; Raja Farzarul Hanim Raja Azmy; Noor Aini Yussoff (Universiti Kebangsaan Malaysia, 2010)
Four species of bacteria, Acinetobacter lwoffii, Aeromonas hydrophila, Pseudomonas aeruginosa and Pseudomonas putida, were isolated from soil contaminated with hydrocarbons and selected for the determination of growth requirements and the ability to degrade petroleum hydrocarbon. The bacteria were grown in mineral salt medium (MSM) supplemented with two types of crude oil, either Sumandak or South Angsi at 1% (v/v) concentration. The optimum pH for growth of A. hydrophila and P. aeruginosa was 6.5 when grown with Sumandak and South Angsi oil. For A. lwoffii and P. putida the optimum pH for growth with Sumandak and South Angsi oil was 6.5 or 7.0, respectively. The growth of P. aeruginosa was the highest in MSM when supplemented with 1% South Angsi oil and 0.5% tryptone at pH 6.5 while, in Sumandak oil the growth was the highest when yeast extract was added. Gas chromatography analysis showed that the South Angsi crude oil components of C12 to C25 were more extensively degraded by A. lwoffii after 24 h of incubation compared to the other bacteria over the same period.